1998
DOI: 10.1128/jb.180.4.969-978.1998
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rhodobacter capsulatus Mutants Affected in Cytochrome cbb 3 Oxidase Activity

Abstract: The facultative phototrophic bacterium Rhodobacter capsulatus contains only one form of cytochrome (cyt)c oxidase, which has recently been identified as acbb3 -type cyt c oxidase. This is unlike other related species, such as Rhodobacter sphaeroides and Paracoccus denitrificans, which contain an additional mitochondrial-likeaa 3-type cyt c oxidase. An extensive search for mutants affected in cyt c oxidase activity in R. capsulatus led to the isolation of at least five classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 58 publications
3
47
1
Order By: Relevance
“…Rhodobacter capsulatus Nadimutants that are not complemented with ccoNOQP-ccoGHIS Screening of Nadi -(i.e. cyt c oxidase deficient) mutants that are not complemented with the ccoNOQP-ccoGHIS gene clusters, known to affect the cbb3-Cox activity, defined a new group of mutants, including MR2, IJ1 (Koch et al, 1998) and AYG4 (Table 1). These mutants exhibited complex phenotypic characteristics (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhodobacter capsulatus Nadimutants that are not complemented with ccoNOQP-ccoGHIS Screening of Nadi -(i.e. cyt c oxidase deficient) mutants that are not complemented with the ccoNOQP-ccoGHIS gene clusters, known to affect the cbb3-Cox activity, defined a new group of mutants, including MR2, IJ1 (Koch et al, 1998) and AYG4 (Table 1). These mutants exhibited complex phenotypic characteristics (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, ccoN::lacZ (pXG2, Koch et al, 1998) andcycY::lacZ (pHM12, Myllykallio et al, 1997) or cycY::phoA (pHM11, Myllykallio et al, 1997) fusions were used to probe whether or not the absence of the c-type cyts was Abbreviations of antibiotic resistances are as follows: Amp, ampicillin; Kan, kanamycine; Rif, rifampicin; Spe, spectinomycin; Tet, tetracycline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inverted cytoplasmic membranes from wild-type R. capsulatus (MT1131) and its mutants were prepared as described previously (Koch et al, 1998a;Pawlik et al, 2010). For Blue Native (BN) PAGE analyses, ICMs (100 mg of total protein) were incubated at 258C for 15 min with continuous shaking (550 rpm Eppendorf Thermomixer), in lysis buffer (50 mM NaCl, 50 mM imidazole/HCl, pH 7.0, 5 mM 6aminohexanoic acid) containing 1% n-dodecylmaltoside (Thermo Scientific Inc.).…”
Section: Preparation Of Intracytoplasmic Membranes (Icms) and Blue Namentioning
confidence: 99%
“…As would be predicted, anaerobic expression of cbb 3 oxidase was increased in the regB mutant, however, the expression level was 2-fold higher than that of the wild-type [98]. This discrepancy was explained when it was shown that FnrL positively regulate the ccoNOQP operon under anaerobic photosynthetic and semiaerobic conditions in both R. capsulatus and R. sphaeroides, possibly acting at a consensus FNRbinding sequence that is centered approximately 100 bp upstream of the ccoN transcription start in R. capsulatus [98,99] and 73.5 and 41.5 bp upstream of the FnrL-dependent P2 N transcription start in the R. sphaeroides cco promoter [37]. In an interesting twist, FnrL was shown to negatively regulate the R. capsulatus cydAB operon under semi-aerobic conditions leading to the speculation that in R. capsulatus, cbb 3 oxidase has a higher affinity for O 2 than quinol oxidase and is therefore, preferentially expressed under low O 2 conditions [98].…”
Section: Reg/prr Regulation Of Electron Transport Componentsmentioning
confidence: 99%